2013
DOI: 10.4103/2152-7806.123656
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial actions of the anti-inflammatory dimethyl fumarate in glioblastomas

Abstract: Background:Dimethylfumarate (DMF), a drug used in the treatment of psoriasis and multiple sclerosis, has been shown to limit the growth of melanoma cells. The ability of DMF to inhibit the Rel protein has been used to explain the antioncogenic properties of this drug. Studies analyzing the effect of DMF in gliomas are limited. Therefore, we investigated the potential antitumor effects of DMF by assessing its effects on proliferation, cell death, and differentiation in gliomas in several glioma models.Methods:M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The observed reductions in cytokine secretion were dose dependent and restricted to DMF; pretreatment with MMF did not significantly reduce cytokine/chemokine production. As fumarates have been previously shown to alter viability and proliferation of peripheral and CNS‐resident cells,8, 28 we assessed whether the changes in cytokine and chemokine levels were due to changes in viability or proliferation. Following pretreatment with DMF, MMF, or vehicle no reductions in viability or proliferation were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observed reductions in cytokine secretion were dose dependent and restricted to DMF; pretreatment with MMF did not significantly reduce cytokine/chemokine production. As fumarates have been previously shown to alter viability and proliferation of peripheral and CNS‐resident cells,8, 28 we assessed whether the changes in cytokine and chemokine levels were due to changes in viability or proliferation. Following pretreatment with DMF, MMF, or vehicle no reductions in viability or proliferation were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both NF‐κB and T1‐IFN pathways are innate immune signaling pathways that are triggered upon viral infection; and the capability of DMF to promote viral spread may stem from its potential to inhibit T1‐IFN production and response, an effect that can be associated with DMF's ability to block NF‐κB nuclear translocation . In brain tumor cells, Ghods et al reported that DMF, at concentrations of 100 to 300 μM, reduced the rate of proliferation in mouse glioma Gl261, human glioblastoma, and A172 cells; and in human glioblastoma cells from patients. DMF also decreased the expression of NF‐κB and restricted the growth of CD133 (a stem cell marker) cells in gliomas .…”
Section: Evidence Of Dmf As An Anticancer Agent: Preclinical Activitimentioning
confidence: 99%
“…It was noted that DMF has additional pharmacological effects such as antioxidant and anticancer activities . The potential benefits of DMF as an anticancer agent, in particular, has been shown in preclinical models of melanoma, breast cancer, cervical cancer, colon cancer, glioblastomas, ovarian cancers, CTCL, and lung cancers . This anticancer effects of DMF have been linked to targeting of a wide range of cellular and molecular pathways involved in cancer pathogenesis including nuclear factor erythroid 2 (NF‐E2)–related factor 2 (NRF2), protein deglycase DJ‐1/Parkinson disease protein 7 (DJ‐1), Kelch‐like ECH‐associated protein 1 (KEAP1), nuclear factor‐κB (NF‐κB), extracellular signal‐regulated kinase 1 and 2 (ERK1/2), and p38 mitogen‐activated protein kinases (MAPKs), phosphatase and tensin homolog (PTEN), p53, and micro ribonucleic acids (miRNA) network.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 DMF, at the approved dose for multiple sclerosis therapy, is rapidly metabolized to mono-methyl fumarate (MMF), and has a C max in plasma of »15 mM, with an approximate steady state tissue and plasma concentration of 5 mM, though many studies using this compound have used the drug at much higher concentrations. 4,[7][8][9][10] In addition to its actions on immune cells, DMF also suppresses the inflammatory biology of microglia and astrocytes. [11][12][13][14][15] As activated microglia and reactive astrocytes play key roles in the biology and progression of GBM tumors in vivo, DMF represents one potential drug which could alter GBM growth and the growth of other tumor types in vivo.…”
Section: Introductionmentioning
confidence: 99%